Understanding NBC weapons in the context of contemporary terrorism. - Koo, Peng Kuan. (2008)
Personnel studying or dealing with unconventional (NBC) weapons, by their natures of originating ultimately first form scientific theories, cannot escape the fact of at least understanding basic principles of their working mechanics in the impact upon operational application.